Optimizing fen peatland water‐table depth for romaine lettuce growth to reduce peat wastage under future climate warming. (8th July 2021) - Matysek, Magdalena; Leake, Jonathan; Banwart, Steven; Johnson, Irene; Page, Susan; Kaduk, Jorg; Smalley, Alan; Cumming, Alexander; Zona, Donatella
Summary: Forty percentage of UK peatlands have been drained for agricultural use, which has caused serious peat wastage and associated greenhouse gas emissions (carbon dioxide (CO2 ) and methane (CH4 )). In this study, we evaluated potential trade‐offs between water‐table management practices for minimizing peat wastage and greenhouse gas emissions, while seeking to sustain romaine lettuce production: one of the most economically relevant crop in the East Anglian Fenlands. In a controlled environment experiment, we measured lettuce yield, CO2, CH4  fluxes and dissolved organic carbon (DOC) released from an agricultural fen soil at two temperatures (ambient and +2°C) and three water‐table levels (−30 cm, −40 cm and −50 cm below the surface). We showed that increasing the water table from the currently used field level of −50 cm to −40 cm and −30 cm reduced CO2 emissions, did not affect CH4  fluxes, but significantly reduced yield and increased DOC leaching. Warming of 2°C increased both lettuce yield (fresh leaf biomass) and peat decomposition through the loss of carbon as CO2 and DOC. However, there was no difference in the dry leaf biomass between the intermediate (−40 cm) and the low (−50 cm) water table, suggesting that romaine lettuce grown at this higher water level should have similar energetic value as the crop cultivated at −50 cm, representing a possible compromise to decrease peat oxidation and maintain agricultural production.